GIS for A-level geography - O'Connor, Peter (Geographical Association, 2008)
Auf dem Umschlag: Geographical Information Systems (GIS) are the most powerful set of tools in existence for the analysis and visualisation of spatial information, and GIS is central to the application of geography to real-world problem solving. Its growing importance is reflected in the recent A-level specifications, all of which include modules that revolve around teaching and understanding methods of geographical investigation. GIS for A-level geography, written specifically for secondary level education, offers A-level geography students an accessible introduction to industry-standard GIS. Produced in collaboration with ESRI (UK), and including ArcView 9.2 software with a 12-month licence and NAVTEQ digital map data for England, Peter O’Connor’s new book is a complete guide to the theory and applications of GIS, with five practical exercises, described step-by-step. The book describes how governments, organisations and individuals are using GIS to grapple with increasingly complex social, economic and environmental problems. It then develops students’ GIS skills through the use of sophisticated GIS software in a way that takes account of both the advantages and limitations of the technology. An understanding of GIS plays a crucial role in introducing students to modern methods of spatial data capture, processing, analysis and presentation. Many chapters in this book, therefore, could be used as case study material to reinforce students’ learning about the different stages of a geographical investigation. Peter O’Connor is Head of Geography at Bishop’s Stortford College and a member of the Geographical Association ICT Working Group.